Re-analysis of the Levänluhta skeletal material: Sex and stature estimation of individuals in an Iron Age water burial in Finland - Maijanen Heli; Junno Juho-Antti; Mannermaa Kristiina; Niskanen Markku; Wessman Anna (WILEY, 2022)
Levänluhta, an Iron Age water burial site in Finland, and its material consisting of commingled skeletal remains and artifacts, has been studied by several researchers over the past 100 years, resulting in multiple interpretations of the people and the site. Previous skeletal analyses have concluded that the majority of the individuals represented in the remains were females and children and were of relatively short stature, so possibly nutritionally deprived. This study re-analyzed the commingled adult human remains with updated methods. The methods applied in this study to estimate sex and stature were based on more representative European reference samples than the previously applied methods. The methods included morphology, osteometrics, and computed tomography (CT) scans. Our results indicated that depending on the reference data, the majority of the individual adult bones including os coxae (73%, n = 45) and long bones (humerus 83%-89%, n = 52; radius 72%-89%, n = 47; ulna 50%-65%, n = 58; femur 92%-100%, n = 25; tibia 77%-85%, n = 26) were classified as females based on their size and morphology. The cross-sectional bone properties of humerii, femora, and tibiae visualized using CT scanning also supported these findings. However, the cranial morphology did not show as clear female-biased sex ratio as other methods (42% females, 33% males, 24% undetermined, n = 33). In females, the mean stature based on the tibia (155.3 cm, n = 10) was within the range of the coeval European females and did not necessarily indicate nutritional deprivation, which is in line with previously published stable isotope findings from the site. The mean stature based on the tibia suggested that the Levänluhta males were short (164.0 cm, n = 3), but final interpretations were limited due to the small number of male individuals. The current study affirmed that the Levänluhta skeletal assemblage was female biased and gave new insights into interpretation of the stature.